2013
DOI: 10.5455/2319-2003.ijbcp20131221
|View full text |Cite
|
Sign up to set email alerts
|

Prescription pattern of drugs in pregnancy induced hypertension in a tertiary care hospital

Abstract: Background: The objective of this study was to evaluate the prescription pattern of drugs in pregnancy induced hypertension in a tertiary care hospital. Methods: A retrospective observational study was conducted by department of Pharmacology in collaboration with the Department of Obstetrics in Kamineni Institute of Medical Sciences, Narketpally after taking permission from the Institutional Review Board. WHO basic indicators were indicators were used for studying the prescribing pattern of drugs. Results: Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…Oral nifedipine and oral methyldopa, at different doses, were the drugs often prescribed. This finding is similar to the findings of Kumar et al where it was observed that both nifedipine and methyldopa are the most prescribed antihypertensives in pregnancy [ 23 ]. Nifedipine is a calcium channel blocker which is effective at reducing blood pressure without uteroplacental blood flow nor slowing foetal heart rate [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Oral nifedipine and oral methyldopa, at different doses, were the drugs often prescribed. This finding is similar to the findings of Kumar et al where it was observed that both nifedipine and methyldopa are the most prescribed antihypertensives in pregnancy [ 23 ]. Nifedipine is a calcium channel blocker which is effective at reducing blood pressure without uteroplacental blood flow nor slowing foetal heart rate [ 24 ].…”
Section: Discussionsupporting
confidence: 92%